RISK ANALYSIS OF FINANCING PUBLIC PASSENGER TRANSPORT - Poliak, Milos (Doprava a spoje, 2011)
The aim of this submission is to point to the possibilities of optimalization of spending of the public sources identified for transport servis by public transport assurance, what were identified at the base of project ``The transport service regional plan processing - pilot study'' solution and authors' following research in relation to the public transport financing.